‘So where are your in-laws from?’: Realities and mental images within the space of Kalmyk wedding rites) - Sharaeva, Tatyana I. (The New Research of Tuva, 2019)
The article examines the ideas of explored space in its relation to differences between wedding rites inherent to diverse sub-ethnic groups of the today Kalmyks. Ethnic and administrative divisions of the Kalmyks have always been closely linked. The term ‘ulus’ denoted both a territorial unit and its ethnically bound population. The space assigned to a certain ulus was constituted by a number of consecutive circles, with the focus in the place of residence of an individual and the community of their kinsfolk. This cultivated area was perceived as one’s ‘own land’, their ‘ancestral territory’. By the early 21st century, Kalmyks have developed a form of perceiving one’s ‘own’ space through the prism of ulus division as imposed on present-day boundaries within the republic. This still serves as a foundation stone of ‘belonging’ to a certain sub-ethnic group ‘determined’ geographically.Such a perception of space among modern Kalmyks - both rural and urban dwellers - is taken into consideration during wedding rites. It stems from the four-part horizontal division of space whereby cardinal points are tied to residential areas of certain sub-ethnic groups. The future wedding and a journey to the potential in-laws, differences in wedding rites, as well as the to-be-delivered food sets and utensils are tied to the concept of ‘otherness’, ‘alienness’, to a temporal shift into a similar but ‘alien’ space marked by the Kalmyk term ‘khӓr γazr’ (Kalm. хǝр һазр). The idea of crossing into and staying in an ‘alien land’ gave rise to compulsory ceremonial offerings to master spirits of the land and ancestors at borders of essential circles connected to the vertical three-part division of space. Reaching the center of an ‘alien land’ and stay in a dwelling has preserved the spatial semantic code of traditional culture. In the ritual landscape the parties must reach a compromise to comply with one’s ‘own laws’.For its sources, the article relies on the materials on wedding rites collected by the author during fieldwork in Kalmykia in 2008-2010 and 2018-2019.
Keywords: Kalmyks; Kalmykia; wedding; wedding rites; in-laws; space; ethnic groups